If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -11 = 3w + -5 Reorder the terms: -11 = -5 + 3w Solving -11 = -5 + 3w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-3w' to each side of the equation. -11 + -3w = -5 + 3w + -3w Combine like terms: 3w + -3w = 0 -11 + -3w = -5 + 0 -11 + -3w = -5 Add '11' to each side of the equation. -11 + 11 + -3w = -5 + 11 Combine like terms: -11 + 11 = 0 0 + -3w = -5 + 11 -3w = -5 + 11 Combine like terms: -5 + 11 = 6 -3w = 6 Divide each side by '-3'. w = -2 Simplifying w = -2
| 4(8+6)=-40 | | 5/15=A/45 | | 3/8h=1/4 | | 3/4a(5a-3)=3/8 | | 4v-5=1+3v | | 12x-7/4 | | 6(k-8)+4(-1-3k)=58 | | 10-3x+10x-7=15 | | x+3-2x=5-7x+1b | | 1/4-1/2=-3/4 | | 7-2q1/2n | | 5/6n=-9 | | 7f-24=5 | | P/5-5/P | | x^3-2x^2+kx+14=0 | | 6x+7=7x+14 | | 7=0.9y | | 3-4(4n+4)=49 | | -18=-6+2w | | 0=x^2-6x+0 | | 40a-5= | | 5x+30=2x+140 | | 6n+4-2n=16 | | 5m+7-m+5=28 | | .05+n*9=16 | | 4(59)=76.5 | | 2-3/4w | | B-4/3=b | | 1/2(x-10)=4 | | 2x+3(-12x+8)=-10 | | 5b+6-6b-2=19 | | 30=5w-5 |